Women And The Cultural Practice Of Anti-Birth Control Pills In The Islamic Community In Surabaya - Ridwan, Ahmad; Susanti, Emy (Opción, 2019)
This study focuses on the cultural practice that is against the use of birth con- trol pills by poor families in the central of Surabaya’s metropolis city within the classical Islamic culture and its associated rules. Social relations and the “Islamic culture” is felt in this place. For example, women must wear a veil in every day, the man wear sarongs and koko shirts and reading the Holy Quran is a habitual activitiy. Men and women of Kyai descent in Sidosermo are called “Mas”. Kyai is a term for men who are religious experts and who become leaders in the Islamic community. In fact, the families in this place do not use birth control pills to maintain the number of births. Reproductive health, especially for women, is not an important thing for them. The methodology used was qualitative. We conducted in-depth interviews with men and women who got married. We also found influential figures who deeply knew about the culture of that community. Using the theoretical model of social reproduction by Pierre Bordieu, social action arises because of habitus and the capital in a given arena. There is a dialectic between the actors and social systems. The study found that the practice within the culture of being anti-birth control pill takes place. The parents always pass on to their children classical Islamic val- ues. This is strengthened in various study groups, that family life must follow Muhammad’s textual teachings. The family system and social environment always try to preserve the surrounding culture. This phenomenon is real and it occurs in the central of a metropolitan city of Surabaya.